Efektivitas Media Audio Visual Dalam Pembelajaran Menghafal Al-Qur’an Pada Anak Kelompok B - Sri Wahyuningsi Laiya; Icam Sutisna; Risa Novila Satingi (Student Journal of Early Childhood Education, 2023)
This research is motivated by the effectiveness of children's learning related to the use of audiovisual media in memorizing the Quran in Group B children at Tk Riyadhus Shalihiin. This research is based on the assumption that audiovisual media in early childhood Quran memorization learning can be effective. This research used a qualitative approach. The data collection techniques employed in this study were observation, interviews, and documentation. The data analysis in this research utilized Miles and Huberman's interactive analysis. Based on the research findings and data analysis, it can be concluded that using audiovisual media in Quran memorization learning is relatively effective and suitable for implementation in early childhood education. However, it is essential to note that the use of audiovisual media should be supplemented with other instructional aids to enhance the Quran memorization abilities of young children. This research proves that audiovisual media is an effective learning tool for memorizing Quran